2022
DOI: 10.1002/adma.202270152
|View full text |Cite
|
Sign up to set email alerts
|

A Readily Scalable, Clinically Demonstrated, Antibiofouling Zwitterionic Surface Treatment for Implantable Medical Devices (Adv. Mater. 20/2022)

Abstract: Harmful microbes can grow freely on implanted medical devices such as catheters (as shown on the right). In article number 2200254, Amir Sheikhi, Richard B. Kaner, and coworkers, report a new method to apply a robust surface coating containing zwitterions, which creates a water layer that prevents biofilm formation (as shown on the left). This can improve the safety of the medical devices and reduce patient complications. Image credit: Amir Sheikhi/Penn State.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Our recent studies have shown that there exist two optimum surface energies for minimum adhesion of bacteria (∼25 mJ/m 2 ) and proteins (∼35 mJ/m 2 ), respectively. , The surface energies of conventional catheter materials and coatings [e.g., silicone, polyvinyl chloride (PVC), hydrogels, and silver] typically fall outside the range of their use, making it impossible to simultaneously repel bacteria and proteins. On the other hand, the recent emergence of biocompatible ultralow-fouling surfaces, including superhydrophilic zwitterionic surfaces, slippery liquid-infused porous surfaces, covalently attached liquid-like surfaces, and superhydrophobic (SH) surfaces, have garnered significant attention and shown great promise in preventing biofouling on medical devices. , Despite working through different mechanisms, these surfaces can form a “dynamic interface” between the surface and foulants (e.g., bacteria and proteins), inhibiting their attachment and propagation or allowing easy detachment under shear flow . To date, numerous studies have reported their success under various conditions, but no research has been conducted to compare their efficacy in preventing CAUTI. Herein, we describe the fabrication of these four types of coatings for urinary catheters and compare their antifouling performance with that of uncoated and hydrogel-coated catheters using a stepwise approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent studies have shown that there exist two optimum surface energies for minimum adhesion of bacteria (∼25 mJ/m 2 ) and proteins (∼35 mJ/m 2 ), respectively. , The surface energies of conventional catheter materials and coatings [e.g., silicone, polyvinyl chloride (PVC), hydrogels, and silver] typically fall outside the range of their use, making it impossible to simultaneously repel bacteria and proteins. On the other hand, the recent emergence of biocompatible ultralow-fouling surfaces, including superhydrophilic zwitterionic surfaces, slippery liquid-infused porous surfaces, covalently attached liquid-like surfaces, and superhydrophobic (SH) surfaces, have garnered significant attention and shown great promise in preventing biofouling on medical devices. , Despite working through different mechanisms, these surfaces can form a “dynamic interface” between the surface and foulants (e.g., bacteria and proteins), inhibiting their attachment and propagation or allowing easy detachment under shear flow . To date, numerous studies have reported their success under various conditions, but no research has been conducted to compare their efficacy in preventing CAUTI. Herein, we describe the fabrication of these four types of coatings for urinary catheters and compare their antifouling performance with that of uncoated and hydrogel-coated catheters using a stepwise approach.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 15 The surface energies of conventional catheter materials and coatings [e.g., silicone, polyvinyl chloride (PVC), hydrogels, and silver] typically fall outside the range of their use, making it impossible to simultaneously repel bacteria and proteins. On the other hand, the recent emergence of biocompatible ultralow-fouling surfaces, including superhydrophilic zwitterionic surfaces, 16 slippery liquid-infused porous surfaces, 17 19 covalently attached liquid-like surfaces, 20 and superhydrophobic (SH) surfaces, 21 have garnered significant attention and shown great promise in preventing biofouling on medical devices. 22 , 23 Despite working through different mechanisms, these surfaces can form a “dynamic interface” between the surface and foulants (e.g., bacteria and proteins), inhibiting their attachment and propagation or allowing easy detachment under shear flow.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] C. albicans biofilms are inherently resistant to the majority of known antifungal drugs, making these infections particularly difficult to treat. [ 24 ] Although many antifungals can penetrate EPS, the cells embedded in the biofilm are often still protected. Antimicrobials require at least some degree of cellular activity to be effective because their mechanism involves the disruption of a microbial process: meanwhile, the polymorphic structure of Candida biofilms leads to slow cell metabolism.…”
Section: Introductionmentioning
confidence: 99%